2013
DOI: 10.1007/s10877-013-9436-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of skin type and wavelength on light wave reflectance

Abstract: DedicationIn dedication to my family, friends, and Jessie for whom I could of not done this without.Their constant support, faith and encouragement provided me with the strength and passion that allowed me to pursue my dreams. They are my foundation and worked just as hard as I did being here for me. Thank you with all my heart and love.v Acknowledgements A very special thanks to Dr. Tanaka my primary investigator and advisor, whom kept me on track and taught me that research, is more than just knowledge; it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
91
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 30 publications
7
91
1
Order By: Relevance
“…Although this would seem to be an obvious area of scrutiny of such devices, data on the accuracy of instantaneous heart rate in people of varied skin pigment using a photoplethysmograph is scarce. These current data agree with Fallow et al [38], who found that green light wavelengths of 530 nm demonstrated the greatest modulation compared to all other wavelengths tested in resting and exercise conditions, regardless of skin type.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although this would seem to be an obvious area of scrutiny of such devices, data on the accuracy of instantaneous heart rate in people of varied skin pigment using a photoplethysmograph is scarce. These current data agree with Fallow et al [38], who found that green light wavelengths of 530 nm demonstrated the greatest modulation compared to all other wavelengths tested in resting and exercise conditions, regardless of skin type.…”
Section: Discussionsupporting
confidence: 93%
“…These data suggest that future research of this nature include a measurement of device proximity to the wrist. Discrepancy may also be owed to the light wavelength used in each device and how they detect heart rate in participants with varied skin types [38]. These concerns will be addressed in the discussion section.…”
Section: Resultsmentioning
confidence: 99%
“…5 indicates that the IRPTT cannot be calculated accurately because of its susceptibility to noise or motion artifacts, despite the subject being in a resting condition. This advantage of the green PPG is consistent with the conclusions from previous studies [13][14][15]. We speculate that this is due to the fact that the light path length of green LED is shorter than that of near-infrared LED.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies indicate that green PPG sensors are more resistant to motion artifacts than near-infrared PPG sensors [13][14][15]. Therefore, a green PPG sensor is often used to estimate the state of blood ow and to measure heart rate.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, light scattering properties of surface of human skin are theoretically studied using Maxwell's equation [10]. The effects of varying level of melanin in light reflectance of a wide range of wavelength are investigated for its applications in biomedical optics such as heart rate monitoring devices [11]. However, the impact of ambient humidity on the optics of the skin is poorly understood.…”
Section: Introductionmentioning
confidence: 99%